Prevalência de sintomas não psicóticos entre profissionais de enfermagem idosos e não idosos no contexto de trabalho durante a Covid-19 - Nogueira, Larissa Santos (Universidade Federal de São Carlos, 2023)
OBJECTIVE: To identify the most prevalent non-psychotic symptoms among nursing professionals arising in the context of the COVID-19 pandemic at work. METHOD: A quantitative, observational and cross-sectional study carried out with support from FAPESP, carried out with nursing workers from public services at three levels of health care in a city in the interior of São Paulo. Data collection took place online through an instrument composed of sociodemographic and labor information and the Self Reporting Questionnaire (SRQ-20) scale, available on the research project's website link. In the descriptive analysis of the data, frequency distributions were estimated. RESULTS: Results were obtained from a sample of 175 nursing professionals, 81.7% women and 18.3% men, with a predominance of Nursing technicians or assistants (62.9%) and a higher prevalence in the age group between 20 and 39 years (56.6%) among the participants. Most participants reported having worked on the front line (78.3%) without taking time off from their activities (68.6%). With regard to mental distress, 93 (53.1%) were positively screened for mental distress using the SRQ-20 scale. The main symptoms reported were: sleeping poorly, feeling nervous, tense or worried, feeling tired all the time, getting tired easily and frequent headaches. FINAL CONSIDERATIONS: It is concluded that despite the pandemic moment being under control, nursing workers are in a situation of mental suffering, presenting non-psychotic symptoms, probably triggered and/or intensified by the previous phases of the pandemic, which requires special attention, constant monitoring and future.
Prevalence of non-psychotic symptoms among elderly and non-elderly nursing professionals in the work context during Covid-19
Keywords: Prevalência; Saúde mental; Profissionais de enfermagem; Infecções por Coronavírus; Enfermagem; Prevalence; Mental health; Nurse practitioners; Coronavirus Infections; Nursing; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM PSIQUIATRICA